Fatores antinutricionais e coeficientes de digestibilidade aparente da proteína de produtos de soja para o pacu (Piaractus mesopotamicus) - Stech, Marcia Regina [UNESP]; Carneiro, Dalton José [UNESP]; De Carvalho, Maria Regina Barbieri [UNESP] (Universidade Estadual de Maringa, 2010)
This study aimed to determine the activities of trypsin inhibitors, hemagglutinant and tannin levels in soybean meal and in raw and processed soy, as well evaluate the protein apparent digestibility coefficient for pacu juveniles. The apparent coefficients of raw, extruded, toasted and milled soy were determined using chromium oxide (0.5%) as marker. A reference diet was created with 26% crude protein and 4,352 kcal kg-1, with each feed containing 30% of the test diet. Feces were collected by abdominal pressure. All analyzed products presented anti-nutritional factors, but the lowest trypsin inhibitor activity was observed in soybean meal. Soy that received thermal treatment presented better digestibility coefficients and lower hemagglutinating activity values than raw soy. No effects of trypsin and tannin inhibitor were observed on the protein digestibility coefficient, but a negative relationship was observed between hemagglutinin levels and protein digestibility coefficient. The use of soybean meal and extruded or toasted soy is recommended for pacu feeding.
Anti-nutritional factors and protein apparent digestibility coefficients of soybeans sources to pacu (Piaractus mesopotamicus)
Keywords: Hemmaglutinin; Soybean process; Tannin; Trypsin inhibitor; Glycine max; Piaractus mesopotamicus